ANALISIS BIDANG KONTAK ANTARA AIR TAWAR DAN AIR ASIN DI DAERAH PESISIR PANTAI PULAU TERNATE DENGAN MENGGUNAKAN METODE GEOLISTRIK (STUDI KASUS DI KELURAHAN KOTA BARU TERNATE) - Salam, Ramdani; Umar, Sudir (Green Earth, 2012)
The decline of freshwater quality in coastal area one of which is caused by the intrusion of seawater inland. The study was conducted to determine the interface between seawater and freshwater in northern coastal areas of Ternate island (case study of Kelurahan Kota Baru) using geoelectric method. By compiling the data in certain formats, the data are applied to Res2DinV. The inversion result will show an overview of resistivity distribution of seawater and freshwater.The result shows that the interface between freshwater and seawater at Kotabaru coastal areas, about 28.6 Ωm - 125Ωm. The interface tends towards the sea, which showed no contamination between freshwater and seawater, Keywords: Coastal, Interface, Geoelectric